From the Marine Corps to college transitioning from the service to higher education - Ventrone, Jillian 1973- (Rowan & Littlefield, 2014)
The recent wars in Iraq and Afghanistan have taken a heavy toll on our military's population. Many returning service members, in preparing to leave the Armed Forces, decide to pursue higher learning. However, education benefits for veterans, while a source of much discussion, also give rise to much frustration and confusion. This guide simplies the transition process. Designed to help Marines navigate the world of higher education and tier available state and federal benefits, this guide will better prepare veterans for tackling their new mission: college. The easy-to-follow format will assist Marines in furthering their educational goals and allow them to get the most out of the available resources.